From regulatory capture to regulatory space? - Watson, M (2013)
The capture of regulators by industry interests was once viewed as the dominant paradigm for failures of regulation. Recently, the financial crisis has re-awoken interest in ‘regulatory capture’ — a term used by the Governor of the Bank of England Sir Mervyn King, among others. In this policy brief, Max Watson, a former director of the Central Bank of Ireland and senior official at the IMF, finds that regulators ‘bought into’ market risk assessments far too extensively, and failed to criticize systemic risks as they built up in banks. The policy brief revisits the idea of regulatory capture to explore the influences that changed financial sector regulation, including new ideological currents, changes in economics and technology, and the incentives affecting legislators and regulators. Whilst the term ‘capture’ may be too one-dimensional to characterize the dynamic process of change that occurred, Watson advocates the need for greater scrutiny at a time when the economic legacy of major regulatory failures may lead governments to rely even more on regulation to secure their policy goals.